2019
DOI: 10.1001/jamafacial.2019.0201
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Concurrent Orbital Floor Repair During Zygomaticomaxillary Complex Fracture Repair

Abstract: scores, 4 vs 8; 95% CI, 0.01 to 7.99; P = .049). The Terzis score for the open mouth smile significantly increased (mean, 2.5 vs 3.85; 95% CI, 0.12-1.34; P = .02) as did the smile index (mean, 7.5 vs 5.6; 95% CI, −3.47 to −0.34, P = .02). Masseter function was normal in all cases. These data are summarized in the Table and the clinical outcomes in 1 case are illustrated in the Figure . Discussion | This study has demonstrated that smile excursion can be substantially improved when the masseteric nerve is used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Wilde et al in their study showed that only two of 19 (10%) zygomaticomaxillary complex fractures required orbital floor reconstruction, according to intraoperative computed tomography findings after zygomatic bone reduction [ 23 ]. Flynn and colleagues demonstrated that, of 1396 patients who underwent operative reduction, 23% of these patients underwent concomitant orbital floor repair [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wilde et al in their study showed that only two of 19 (10%) zygomaticomaxillary complex fractures required orbital floor reconstruction, according to intraoperative computed tomography findings after zygomatic bone reduction [ 23 ]. Flynn and colleagues demonstrated that, of 1396 patients who underwent operative reduction, 23% of these patients underwent concomitant orbital floor repair [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…17 As a result, there has been a growing trend towards nonoperative management in concurrent orbital floor repair during zygomaticomaxillary complex fracture repair. 18 Orbital displacement is a complex process that is not only affected by increases in orbital volume, but also by atrophy of orbital contents which include fat, muscles, ligaments, and the globe itself. Volume loss from ischemic liponecrosis of endo-orbital fat plays a major role in GMP and PE.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In these cases, there are objectives beyond the orbital reconstruction, restoring neighboring bones, for example, the superior lateral of zygoma, which forms the inside, floor and outside of the orbital wall or the superior border of the maxilla, etc. (Flynn et al , 2019; Kanthak, 1940; Scholz et al , 2007).…”
Section: Introductionmentioning
confidence: 99%